Desenvolvimento e capacidade fitoextratora de plantas agrícolas cultivadas em solo com diferentes texturas e teores de cobre - Silva, Juliano Cesar da (2019)
The addition of copper by anthropic activities influences the metal content of the soil, making this element potentially toxic to agricultural species. The dynamics of copper in the soil is influenced by the physical and chemical characteristics of the soil as well as the activity of symbiotic microorganisms associated with different cultures. Therefore, this work had as objective to analyze the influence of the contamination by copper, evaluating its dynamics in soils with different textures in the cultivation of soybean and sorghum. In order to meet this objective, three experiments were developed: the first evaluated the development of agricultural plants cultivated in soil with different textures and copper contents; the second tested the phytoextractive capacity of agricultural plants cultivated under different percentages of clay and how this affected copper levels in contaminated soils and the third determined the interference of a nitrogen fixing bacteria in the development of sorghum in soil contaminated with copper. The results showed that the soybean and sorghum crops are negatively influenced by the addition of copper in the soil, and its content is affected by soil texture. Soils with 17.5% of clay allow greater availability of copper under conditions of lower Pseudo-total. The more clayey the soil, the greater the amplitude between available copper and Pseudo-Total. The increase of copper in the soil has a positive interaction with the increase of this metal in the soybean grain, so areas contaminated with copper can be considered unsuitable for the cultivation of this species. The inoculation with Azospirillum brasilense allows greater development of the aerial part of the sorghum and reduces the content of copper in aerial part.